Information Communication Technology for Extension: A Mobile Phone Based Voice Call System for Dissemination of Cotton Production Technologies. Issue 1 (2nd January 2019) - Singh, Satnam; Sangwan, Omender; Meena, Bhagwan Singh; Tuteja, Om Prakash; Singh, Harinder Pal; Kumar, Rishi; Pandher, Suneet; Kumar, Surender; Singh, Kulvir; Rathore, Pankaj
ABSTRACT: Dissemination of newer crop production technologies among growers is the major bottleneck in the existing extension system. This study proposes an innovative method for dissemination of cotton cultivation technologies through mobile phones. The voice advisories on different aspects of cotton cultivation were sent to mobile phones of growers, as and when required in the field. Feedback from growers revealed it as a highly acceptable extension technique, which helped them to make crucial time-specific decisions for crop management. The system has the potential to reach and benefit each and every grower at a very low cost compared to conventional training and visit extension system.